The Efficacy of Clove Seed Extracts as an Anaesthetic Agent and Its Effect on Haematological Parameters of African Catfish (Clarias Gariepinus) - Ojo Andrew Akinrotimi; Ugwemorubong Ujagwun Gabriel; Olajumoke Modupe Edun (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2015)
Background and Aim: The intensive nature of aquaculture has subjected fish to a number of stressors in the culture medium, anesthetics are widely used to minimize the issue of stress during farming operations and activities. Clove oil is a well known, established and acceptable anesthetics commonly used in aquaculture, this anesthetics is not readily available in developing countries, thus leaving the fish farmers with option of using the locally available plant extracts as anesthetic agent in fish culture. This study therefore assessed the efficacy of aqueous extracts of clove seed and its effect on hematological parameters of the fish. Methods: A total of 300 Clarias gariepinus comprises of 150 juveniles and 150 adult fish were exposed in triplicates to aqueous extracts of clove seed at concentrations of 5.0, 10.0, 15.0, 20.0 and 25.0mg/l at the rate of 10 fish per tank for both juveniles and adult fish. Induction time (Time taken for the fish to be completely anaesthetized) and recovery time (Time taken for the fish to resume normal swimming) was monitored using stop watch. Also, the effect of the extracts on water quality, survival and hematological parameters of the fish were evaluated using standard methods. Results: The result obtained revealed that the induction time indicated a size related response with the adult fish significantly (P<0.05) higher than the juveniles at all concentration of exposure. However, reverse was the case in recovery time, as the recover times in juveniles were higher than the adult fish. The survival was 100% in both sizes. Significant alterations were recorded in the haematological variables of the fish, which was more pronounced at higher concentrations of the extracts. Conclusion: The extract was effective in sedating C.gariepinus and is recommended for use as an aesthetic agent.